The United States and the rise of China: The strategy of the Bush administration - Peter Rudolf (Stiftung Wissenschaft und Politik (SWP), 2006)
In light of the uncertainties associated with the further rise of China, the US has found a 'rational' strategic plan under President George W. Bush that is politically acceptable within the administration and to the domestic public at large. It combines elements of engagement and containment in a policy of 'congagement.' The aim of American strategy is to further integrate China into the international system and to incorporate the country as a constructive actor within a concert of great powers under US leadership. This strategy, however, does not presuppose that the further rise of China will necessarily occur peacefully. Rather, America's strategy allows for the possibility of the development of an antagonistic rivalry for hegemony. The US policy of political cooperation and economic integration is accompanied by a noticeable increase in strategic hedging. Maintaining American military supremacy and the expansion of security relationships with states in the Asia-Pacific region have become central elements of this hedging under President Bush. The American strategy is to structure the international system such that the Chinese leadership's cost-benefit analysis will lead it to prefer cooperative relations with the US in the long run. (SWP-Research Papers / SWP)
Keywords: 320